First report of Leucostoma cinctum on sweet cherry and European plum in Italy - ROMANAZZI, Gianfranco; MANCINI, Valeria; MUROLO, Sergio (Phytopathologia Mediterranea, 2012)
Leucostoma cinctum and L. persoonii are the two species involved in Leucostoma canker, a disease that causes dieback of twigs and branches, bark cankers, gummosis, and tree decline of stone fruit. The aim of this study was to identify the causal agent of Leucostoma canker in Italian stone fruit orchards. More than 200 isolates of Leucostoma spp. were obtained from branches and twigs of sweet and sour cherry, apricot, and European plum trees that showed typical symptoms of Leucostoma canker. These trees were in commercial orchards of two Italian regions, Marche and Apulia, in central-eastern and south-eastern Italy, respectively. Soon after isolation, all of the colonies that grew on potato dextrose agar were white in colour, and after about 10 d they became olive-green. Growth was not observed at 33°C, and the pycnidia were larger than 1 mm diam. This information led to the identification of L. cinctum as the causal agent of these Leucostoma cankers. To our knowledge, this is the first report of L. cinctum on sweet cherry and European plum in Italy.